Community-based natural resource management - Menon, Ajit (Sage, 2007)
Introduction -- Hivre Bazar -- Utthan's Work in Nathugadh, Gujarat -- Community-based Natural Resource Management in Gopalpura, Rajasthan -- Community-based Natural Resource Management in Bhutan -- Community-based Natural Resource Management in the Central Himalayas -- Sustainable Livelihoods in Riverine Charlands -- Conclusion